The impact of culture in international projects - Ragnheiður Ásgrímsdóttir 1967- (2017)
Over the last decades, we can say the world has become smaller, among other things due to globalization, new technology, and better transportation. Organizations are seeking new markets, open economic areas with people working in different countries, and increasingly working in cross-border projects. The international growth of Icelandic companies has also been extremely fast in the last fifteen years (Adalsteinsson & Gudlaugsson, 2007) and has brought new challenges to the Icelandic working environment. A case study was conducted at Össur, an international non-invasive orthopaedics company, with its headquarters located in Iceland. Five employees were interviewed and results from retrospective meetings are also part of the research. The findings of the research indicate that national culture has an impact on the progress of international projects and needs to be further investigated. Icelandic culture by itself, when Icelandic project managers are leading international projects, does not have an impact on the progress of the project; it´s more the fact that all project managers need to train themselves in leadership, being adaptable, flexible and having the ability to understand each individual of a project team and respect their opinion that matters. Another finding of this research is that organizational culture can have an even larger impact on the progress of the project, especially if the organizational structure is dysfunctional in some way.